Hukum Jual Beli Saham BRIS di Komunitas Syariah Saham dalam Perspektif Hukum Islam dan Positif - Zamaluddin Zamaluddin; Abdul Rochim; Mabruri Andatu; Rifki Saputra (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Sharia shares are a form of ordinary shares which have special characteristics in the form of strict control regarding the halal scope of business activities. One of the shares listed on the stock exchange belongs to BRI Syariah. Bri Syariah is a sharia bank that has sharia shares. BRI Syariah with the ticker BRIS conducted an initial share offering. Currently, many people are interested in BRIS shares. The increase in BRIS shares is due to the increasing number of people showing interest in sharia finance. Sharia capital markets are capital market activities that do not conflict with sharia principles in the capital market. The explanation of the phenomena stated above provides a gap that requires urgent further research related to the law of buying and selling BRIS shares in the sharia share community from the perspective of Islamic and positive law. This research is normative juridical research that is qualitative in nature. Normative juridical research is a process for determining legal rules, legal principles and legal doctrines. In this research, the approach used is a statutory approach and an analytical approach. From the results of the author's research, it was found that the process of buying and selling BRIS shares from an Islamic legal perspective must avoid several aspects, namely Bai' al-Hamisy and Bai' al-Maksyuf. The practice of buying and selling BRIS shares in the Sharia Shares Community begins with a contract process that is adapted to DSN-MUI No.80 of 2011 and the process of buying and selling BRIS shares from a positive legal perspective has been carried out safely and in accordance with Financial Services Authority (OJK) regulations. buying and selling BRIS shares is permitted based on the perspective of Islamic law. The perspective of Islamic law regulates that buying and selling must avoid several aspects, namely Bai' al-Hamisy and Bai' al-Maksyuf. The practice of buying and selling BRIS shares in the Sharia Shares Community begins with a contract process adapted to DSN-MUI No.8 of 2011, namely mudharabah, ijarah, musyarakah and syirkah contracts.